Effect of Sources and Inclusion Levels of Zinc in Broiler Diets Containing Different Vegetable Oils During Summer Season Conditions on Meat Quality - Selim, N.A.; Amira M. , Refaie,; Khosht, Abeer R.; El-Hakim, A.S. Abd (International Journal of Poultry Science, 2014)
The aim of this study was to evaluate the interactions between different dietary fatty acids’ (FAs) patterns, zinc sources and levels on carcass and meat quality traits of Cobb 500 broiler chicks. Broilers were fed diets contained two different oil sources (soybean oil mainly composed of unsaturated fatty acids, SO; or palm oil mainly composed of saturated fatty acids, PO) and within each studied FAs source, three sources of zinc (zinc sulphate, ZS; zinc methionine, ZM; or nano-zinc oxide, NZO), each at two levels, Recommended (R) equals to 100 mg Zn/kg diet for both ZS and ZM and 40 mg/kg diet for NZO or high (H) equals to 200 mg Zn/kg diet for both ZS and ZM and 80 mg/kg diet for NZO) in a factorial arrangement of 2 x 3 x 2. Results reveal that chicks fed diets contained SO had significantly lower percentage of thigh skin, while, it had higher drip loss and ultimate pH (pHu) of breast and thigh muscles and significantly improved all sensory values of cooked meat compared to those fed diets containing PO. While, those fed dietary PO significantly recorded lower MDA in meat compared to the others fed diets contained SO. Birds fed NZO diets significantly recorded the lowest carcass, breast and thigh skin percentages. Also, it significantly reduced breast drip loss and significantly enriched their meat with zinc by 41.4 and 10.6%, respectively relative to other two zinc sources. Concerning zinc levels, there were no significant differences between the two levels in all parameters studied except in muscles Zn content which was significantly increased by increasing dietary Zn level while, high dietary Zn level significantly reduced total lipids in muscles. It could be concluded that among the examined factors using palm oil, nano zinc oxide at level of 80 mg/kg diet improved carcass traits and meat quality of broiler reared under summer season conditions. While more researches concerning using nano-elements in broiler diets and its safety to human consumption are needed.